2013
DOI: 10.1136/annrheumdis-2013-203915
|View full text |Cite
|
Sign up to set email alerts
|

Identification of anticitrullinated protein antibody reactivities in a subset of anti-CCP-negative rheumatoid arthritis: association with cigarette smoking and HLA-DRB1 ‘shared epitope’ alleles

Abstract: IntroductionA hallmark of rheumatoid arthritis (RA) is the development of autoantibodies targeting proteins that contain citrulline. Anticitrullinated protein antibodies (ACPAs) are currently detected by the commercial cyclic citrullinated peptide (CCP) assay, which uses a mix of cyclised citrullinated peptides as an artificial mimic of the true antigen(s). To increase the sensitivity of ACPA detection and dissect ACPA specificities, we developed a multiplex assay that profiles ACPAs by measuring their reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
50
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 26 publications
11
50
0
1
Order By: Relevance
“…Applying the antigen-centric model, the transition of an anti-native protein to an anti-citrullinated protein antibody response may depend on the presence of permissive factors, that is, a genetic predisposition allowing for presentation (HLA alleles) and the continued production of modified antigen (chronic bacterial infection, smoking or immune-mediated membranolysis resulting in secondary release of modified autoantigens into the extracellular compartment of the RA joint) 4 36 38 39 40. In the individual at risk, concurrence of these factors, timing and stochastic events may define whether antibody transition occurs during the pre-RA phase, once the disease is established, or not at all (ACPA-negative RA).…”
Section: Discussionmentioning
confidence: 99%
“…Applying the antigen-centric model, the transition of an anti-native protein to an anti-citrullinated protein antibody response may depend on the presence of permissive factors, that is, a genetic predisposition allowing for presentation (HLA alleles) and the continued production of modified antigen (chronic bacterial infection, smoking or immune-mediated membranolysis resulting in secondary release of modified autoantigens into the extracellular compartment of the RA joint) 4 36 38 39 40. In the individual at risk, concurrence of these factors, timing and stochastic events may define whether antibody transition occurs during the pre-RA phase, once the disease is established, or not at all (ACPA-negative RA).…”
Section: Discussionmentioning
confidence: 99%
“…Smoking has also been strongly linked to the development of anti-citrullinated protein antibodies (ACPAs) commonly seen in RA patients [101], including RA patients who are negative for anti-CCP [102]. Recent research has suggested that periodontitis and P. gingivalis infection are associated with citrullination through the action of peptidylarginine deiminase [87,103].…”
Section: Autoimmune Diseasementioning
confidence: 98%
“…Synthetic peptides which represent lipoprotein epitopes are in the unprocessed form. Each antigen marker was conjugated to spectrally distinct beads using Luminex technology and established methods (23). The pooled antigen panel was incubated with serum samples, and binding was separately assayed using anti-human IgG conjugated to phycoerythrin (PE) or anti-human IgM-PE.…”
Section: Methodsmentioning
confidence: 99%
“…Multiplex approaches have the potential to improve sensitivity and specificity of the current technology by assessing antibody responses to multiple B. burgdorferi proteins and these novel peptide markers simultaneously (21)(22)(23)(24)(25). Such platforms may detect cases where a patient is not responsive to the main immunodominant epitope, where the infecting subspecies of B. burgdorferi is polymorphic at the immunodominant epitope, or where temporal variations in antigen or antibody limit tests based on singleantibody detection (26).…”
mentioning
confidence: 99%